Possibilities for the substitution of the mineral fertilizers with organic manure in the Republic of Macedonia - Lozanovski, Risto; Jekić, Milan (Macedonian Journal of Ecology and Environment, 1997)
Average yearly production of the organic manure from the all kinds of animals in the Republic of Macedonia is estimated to be 2890766 tons or 15807 tons of N, 9981 tons of P,05 and 14564 tons of K20. The average annual needs of nutrients for the crop production in the Republic were estimated to be: 50990 tons of N, 41060 tons of P205 and 44130 tons of K20. It means that organic manure may substitute cca 31% of N, 24% of’P,05 and 33% of K20.